Interferon-alpha prevents apoptosis of endothelial cells after short-term exposure but induces replicative senescence after continuous stimulation. - Pammer, Johannes; Reinisch, Christine; Birner, Peter; Pogoda, Kristin; Stürzl, Michael; Tschachler, Erwin (Laboratory Investigation, 2006)
Although the antiangiogenic activity of type I interferons (IFN) is well known, the mechanism by which it occurs is unclear. In the present study, we have investigated effects of short-term and long-term IFN-alpha exposure on different types of endothelial cells (EC). Short-term IFN-alpha treatment resulted in a distinct reduction of apoptosis of serum and growth factor starved HUVEC and HDMEC. This was accompanied by a strong upregulation of the IFN inducible guanylate binding protein-1 (GBP-1) whereas no consistent regulation of several known antiapoptotic proteins was evident. Stable transfection of HUVEC with an expression vector for GBP-1 mimicked the protective effect of IFN-alpha, suggesting that GBP-1 may contribute to the inhibition of apoptosis. When IFN-alpha, together with serum and EC growth factors, was present continuously a decrease of population doublings by more than 40% was observed in both HDMEC and HCAEC. In addition, the cells displayed a senescent phenotype significantly earlier than control cells and showed an increased adherence for monocytes. Our findings suggest that the antiangiogenic effect of IFN-alpha is mediated by inducing EC senescence rather than EC apoptosis. Furthermore IFN-alpha released in chronic inflammatory conditions might contribute via its prosenescent activity to the pathogenesis of atherosclerosis.